PINK1‐Dependent Mitophagy Regulates the Migration and Homing of Multiple Myeloma Cells via the MOB1B‐Mediated Hippo‐YAP/TAZ Pathway. Issue 5 (23rd January 2020) - Fan, Shengjun; Price, Trevor; Huang, Wei; Plue, Michelle; Warren, Jonathan; Sundaramoorthy, Pasupathi; Paul, Barry; Feinberg, Daniel; MacIver, Nancie; Chao, Nelson; Sipkins, Dorothy; Kang, Yubin
Abstract: The roles of mitochondrial dysfunction in carcinogenesis remain largely unknown. The effects of PTEN‐induced putative kinase 1 (PINK1)‐dependent mitophagy on the pathogenesis of multiple myeloma (MM) are determined. The levels of the PINK1‐dependent mitophagy markers PINK1 and parkin RBR E3 ubiquitin protein ligase ( PARK2) in CD138 + plasma cells are reduced in patients with MM and correlate with clinical outcomes in myeloma patients. Moreover, the induction of PINK1‐dependent mitophagy with carbonylcyanide‐ m ‐chlorophenylhydrazone (CCCP) or salinomycin, or overexpression of PINK1 leads to inhibition of transwell migration, suppression of myeloma cell homing to calvarium, and decreased osteolytic bone lesions. Furthermore, genetic deletion of pink1 accelerates myeloma development in a spontaneous X‐box binding protein‐1 spliced isoform ( XBP‐1s ) transgenic myeloma mouse model and in VK*MYC transplantable myeloma recipient mice. Additionally, treatment with salinomycin shows significant antimyeloma activities in vivo in murine myeloma xenograft models. Finally, the effects of PINK1‐dependent mitophagy on myeloma pathogenesis are driven by the activation of the Mps one binder kinase activator (MOB1B)‐mediated Hippo pathway and the subsequent downregulation of Yes‐associated protein (YAP)/transcriptional co‐activator with PDZ‐binding motif (TAZ) expression. These data provide direct evidence that PINK1‐dependent mitophagy plays a critical role in the pathogenesis of MM and is a potential therapeutic target. Abstract : The important role of PTEN‐induced putative kinase 1 (PINK1)‐dependent mitophagy in regulating multiple myeloma progression and its effects on the Mps one binder kinase activator (MOB1B) Hippo‐Yes‐associated protein (YAP)/transcriptional co‐activator with PDZ‐binding motif (TAZ) pathway are summarized, with an emphasis on myeloma cell homing and migration. This study provides fundamental insights and offers critical knowledge the future translational applications.